Self-Concept and Language Development in Two Dyslexic Children between the Ages of 6 and 12 - Siti Latifah (The Center for Disability Studies and Services Brawijaya University, 2019)
Self-concept is the image that people have about themselves. Each person has both positive and negative self-concept, including children with dyslexia who face obstacle in language development. This research aims to characterize self-concept and language development in two dyslexic children between the ages of 6 and 12. This research applies qualitative case study methodology. The data were collected using the attitude scale and observation. The data were analyzed using descriptive statistics technique. The subjects of this research were two dyslexic children. The result of the research shows that (1) SK, 7 years old dyslexic child who has below average language development and low self-concept; (2) YD, 9 years old dyslexic child who also has below average language development and low self-concept.